Diffusion-weighted MR imaging findings in an isolated abscess of the clivus - Soares-Fernandes, JP; Valle-Folgueral, JM; Morais, N; Ribeiro, M; Moreira da Costa, JA (My University, 2008)
We report the finding of restricted diffusion in an isolated abscess of the clivus and discuss the imaging differential diagnosis, with an emphasis on the usefulness of diffusion-weighted imaging.
Keywords: Abscesso Cerebral; Imagem de Difusão por Ressonância Magnética